Plant Fungal Diseases and Crop Protection (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Fungi are the largest group of plant pathogens, infecting hosts through leaves, seeds, and the soil. These pathogens inflict significant damage on crops through various methods of attack, leading to reduced global production and an ongoing need for new control strategies. The comprehensive approach to managing these crop diseases relies on a deep understanding of the fungi involved, the susceptible growth phases, and the environmental conditions that influence disease development. Public concerns about using synthetic chemicals and the emergence of fungicide-resistant fungal strains have led to a pressing need to explore alternative, environmentally friendly methods. This collection highlights recent innovations and scientific advancements in the study of plant-pathogenic fungi, with a particular focus on their impact on modern agriculture. It also considers the role of non-pathogenic microorganisms that coexist with plants, as these organisms may modulate the onset and severity of disease in complex ways. By deepening our understanding of fungal interactions within the plant microbiome, this research collection offers not only practical solutions for disease control but also a foundation for future scientific exploration.